A shared strategy for a firm and lasting peace - Fernández De Soto, Dr. Guillermo (2016)
Words of the Colombian Minister of Foreign Affairs, Dr. Guillermo Fernández De Soto, before the Support Group for the Peace Process. Madrid, July 7, 2000.